Postpartum ovarian activity and anovulatory estrus in primiparous crossbred cows in the venezuelan tropics - Ramírez Iglesia, Lílido; Soto Belloso, Eleazar; González Stagnaro, Carlos; Soto Castillo, Gustavo; Rivero Urdaneta, Edmundo (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Progesterone (P4) profiles were studied in 61 crossbred primiparous postpartum dairy cows with normal parturition. Cows were located in a dry tropical environment (29.5ÂºC and 1,048 mm annual precipitation), grazing in Guinea grass (Panicum maximum) and Survenola grass (Digitaria xumfolozi) supplemented with concentrate feeding according to milk production level, and body condition. The first postpartum estrus (FPE) was detected by visual observation twice a day. Rectal examination was performed once a week. Milk samples were taken twice a week beginning seven days postpartum. P4 levels in skim milk were determined by radioimmunoassay, as an indicator of ovarian activity (â‰¥ 5 ng/ml). A first progesterone secretion (FPS) prior to the First Postpartum Estrus (FPE) was observed in 50.8% of the cows at 42 Ó 27 postpartum days (ppd). This FPS was â‰¤ 10 days in the 87.1% of the cases and 11-17 days in the rest of the animals (12.9%). The FPE was detected at 56 Ó 32 ppd; 10.9% of the FPE were anovulatory estrus (AE). Cows with AE were more frequently observed before 45 ppd. Only 38.2% of the FPE was detected prior to 45 ppd; the FPE was observed whitin 60 postpartum days in the 68.8% of the cows. Six cows (9.8%) were in luteal phase while 1.64% had persistent high P4 values ( > 24 days) during the calving to FPE interval. An agreement of 44.64% was observed between P4 levels â‰¥ 0.5 ng/ml and a detectable corpus luteum, and 84.74% after FPE. The FPE and P4 level â‰¥ 0.5 ng/ml interval was 7.4 Ó 3.6 days. Â